2009
DOI: 10.1086/597806
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Factor H–Binding Protein Variants Expressed by Epidemic Capsular Group A, W‐135, and X Strains from Africa

Abstract: Background Meningococcal epidemics in Africa are generally caused by capsular group A strains, but W-135 or X strains also cause epidemics in this region. Factor H–binding protein (fHbp) is a novel antigen being investigated for use in group B vaccines. Little is known about fHbp in strains from other capsular groups. Methods We investigated fHbp in 35 group A, W-135, and X strains from Africa. Results The 22 group A isolates, which included each of the sequence types (STs) responsible for epidemics since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 49 publications
0
50
0
Order By: Relevance
“…For example, isolated epidemic strains from serogroups A, W, and X (a recently identified cause of IMD in Africa, for which no vaccine exists), express fHbp proteins that share significant sequence homology with the fHbp antigen used in the 4CMenB vaccine and, therefore, may be susceptible to the bactericidal activity of 4CMenB-induced antibodies. 28,29 Indeed, results of an analysis of the bactericidal activity of sera from 4CMenB-vaccinated individuals against a panel of serogroup X epidemic strains indicated that 4CMenB may indeed confer protection against strains of this serogroup, and that this protection is likely attributable to fHbp-specific antibody responses. 30 While 4CMenB coverage of non-serogroup B strains has not been studied extensively, the susceptibility of any meningococcal strain to bactericidal antibodies elicited by 4CMenB is dependent upon both the degree of similarity between vaccine antigens and the respective target proteins, as well as the expression level of the target proteins, in each strain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, isolated epidemic strains from serogroups A, W, and X (a recently identified cause of IMD in Africa, for which no vaccine exists), express fHbp proteins that share significant sequence homology with the fHbp antigen used in the 4CMenB vaccine and, therefore, may be susceptible to the bactericidal activity of 4CMenB-induced antibodies. 28,29 Indeed, results of an analysis of the bactericidal activity of sera from 4CMenB-vaccinated individuals against a panel of serogroup X epidemic strains indicated that 4CMenB may indeed confer protection against strains of this serogroup, and that this protection is likely attributable to fHbp-specific antibody responses. 30 While 4CMenB coverage of non-serogroup B strains has not been studied extensively, the susceptibility of any meningococcal strain to bactericidal antibodies elicited by 4CMenB is dependent upon both the degree of similarity between vaccine antigens and the respective target proteins, as well as the expression level of the target proteins, in each strain.…”
Section: Discussionmentioning
confidence: 99%
“…We chose FHbp ID 22, as this sequence variant was prevalent in invasive isolates from Africa (14,20) and the immunogenicity of vaccines containing FHbp ID 22 previously had been tested in mice (6,14,16,21). The L130R substitution increased the T m of the N-terminal domain by 7.7°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The same study also evaluated the distribution of fHBP proteins in other meningococcal serogroups (MnC, MnY, and MnW135) and showed that for these other serogroups the proportion of fHBP subfamily A variants was also increased. Relatively more subfamily A disease has also been identified for MnC isolates from South Africa and for W135 isolates from the sub-Saharan meningitis belt in Africa (36,38,39). Conversely, in South Africa, MnW135 is dominated by a higher proportion of fHBP subfamily B variants.…”
Section: Distribution and Diversity Of Fhbpmentioning
confidence: 99%